2001
DOI: 10.1097/00005373-200104000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous rFVIIa Administered for Hemorrhage Control in Hypothermic Coagulopathic Swine with Grade V Liver Injuries

Abstract: rFVIIa reduced blood loss and restored abnormal coagulation function when used in conjunction with liver packing in hypothermic and coagulopathic swine. No adverse effects were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
96
2
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(107 citation statements)
references
References 63 publications
5
96
2
4
Order By: Relevance
“…Animal models have shown that rFVIIa effectively decreases blood loss at trauma [45] and also increased evidence of its efficacy at trauma patients was found [46,47]. In a multicentre, double-blind, prospective, randomized, placebo-controlled trial rFVIIa was shown to be effective and safe in reducing PRBCs transfusion especially in blunt trauma patients, as well as showing a good safety profile [48] when used as an adjunct to trauma care [49].…”
Section: Optimal Treatment Of Critical Bleeding In Traumamentioning
confidence: 99%
“…Animal models have shown that rFVIIa effectively decreases blood loss at trauma [45] and also increased evidence of its efficacy at trauma patients was found [46,47]. In a multicentre, double-blind, prospective, randomized, placebo-controlled trial rFVIIa was shown to be effective and safe in reducing PRBCs transfusion especially in blunt trauma patients, as well as showing a good safety profile [48] when used as an adjunct to trauma care [49].…”
Section: Optimal Treatment Of Critical Bleeding In Traumamentioning
confidence: 99%
“…Finding an intravenous treatment that could assist endogenous clotting mechanisms is therefore a major mission for military researchers. The possibility that hemostatic agents might be useful in reducing blood loss following traumatic injury has received new impetus from the recent use of rFVIIa in both animal models of traumatic injury [8][9][10][11][12][13][14] and in human patients who have suffered traumatic injury [15][16][17]. Although rFVIIa holds promise for such indications, it is also very expensive and is not yet approved for a trauma indication.…”
Section: Introductionmentioning
confidence: 99%
“…It does not appear that rFVIIa induces a generalized hypercoagulability but that its action is limited to the site of injury [5,[11][12][13]. Preliminary results in both animal and human subjects indicate that rVIIa may also play a beneficial role in the treatment of hemorrhage control in cases of trauma [13][14][15][16][17][18][19], although this is not a universal finding [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%